Electric field-enhanced coupled with metal-free peroxymonosulfate activactor: The selective oxidation of nonradical species-dominated system. (1st December 2022) - Yu, Chao; Zhao, Zhenyu; Zong, Yang; Xu, Longqian; Zhang, Bing; Wu, Deli
Highlights: A remarkable synergistic effect was found between electrolysis and conventional Boron/PMS system. Electrolysis converted free radical dominated process to nonradical dominated process. The accelerated self-decomposition behavior of PMS near the cathode interface generated 1O2. E-Boron/PMS system exhibited high selectivity for SMX removal in the presence of common substrates in aqueous system. Abstract: Nowadays metal-free persulfate-based advanced oxidation processes (AOPs) have been intensively investigated, however, the catalysts are often too complex to fully consider their application potential. Conventional AOPs usually suffer from severe interference in real water matrix, thus, selective oxidation is practically and scientifically challenging as it could avoid unnecessary inputs of energy and possible secondary pollutants. In this study, a remarkably synergistic effect was achieved when conventional amorphous boron/peroxymonosulfate (Boron/PMS, 0.67 × 10 −2 min −1 ) system was combined with electrolysis (E-Boron/PMS, 1.54 × 10 −2 min −1 ) to degrade sulfamethoxazole (SMX). Evidenced by selectively quenching tests with kinetic evaluation, electron paramagnetic resonance (EPR), solvent-exchange experiment and electrochemical analysis, the dominated reactive oxygen species in E-Boron/PMS system tended to be 1 O2, instead of the OH and SO 4 − . Mechanistic study unveiled that 1 O2 was generated via accelerated PMS self-decomposition, triggered by interface alkalization and hydroxyl radicals transfer at the cathode interface. 1 O2 is considered to be selective to the electron-rich organic compounds, thus E-Boron/PMS system was superior to conventional radical-dominated system (Boron/PMS) for SMX removal in the co-presence of common inorganic anions, showing the great merits of selective oxidation in nonradical system. These findings provided new insights into effective and selective oxidation of SMX via E-Boron/PMS system, which shed new light on the development of nonradical system. Graphical abstract: Image, graphical abstract